2006
DOI: 10.1007/s10571-006-9013-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Swelling on TRH and Oxytocin Secretion From Hypothalamic Structures

Abstract: 1. Cell swelling induces exocytosis of material stored in secretory vesicles resulting in a secretory burst of peptidic hormones or enzymes from various types of cells including endocrine cells and neurons. We have previously shown that swelling-induced exocytosis possesses limited selectivity; hypotonic medium evokes TRH but not oxytocin release from hypothalamic paraventricular nucleus (PVN) and neurohypophysis (NH). 2. It is the aim of this study to ascertain whether the swelling-induced oxytocin secretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Under our experimental conditions, both neuropeptides are secreted into medium from the same tissue explants, though most likely from different neurons: parvocellular and magnocellular for TRH and oxytocin respectively. As expected TRH secretion was stimulated by cell swelling [29,[36][37][38]61], while oxytocin, neurohormone engaged in water and salt regulation, was not released after cell swelling-inducing stimuli; hypotonicity or ethanol in isosmotic medium [38]. This is in good agreement with observations that ethanol inhibits the release of oxytocin from the posterior pituitary induced by high K + [71] or suckling [72] and that hypotonic stimuli hyperpolarize magnocellular neurosecretory cells via stretch-inactivated channels [73].…”
Section: Specificity Of Cell Swelling-induced Peptide Secretionsupporting
confidence: 86%
See 4 more Smart Citations
“…Under our experimental conditions, both neuropeptides are secreted into medium from the same tissue explants, though most likely from different neurons: parvocellular and magnocellular for TRH and oxytocin respectively. As expected TRH secretion was stimulated by cell swelling [29,[36][37][38]61], while oxytocin, neurohormone engaged in water and salt regulation, was not released after cell swelling-inducing stimuli; hypotonicity or ethanol in isosmotic medium [38]. This is in good agreement with observations that ethanol inhibits the release of oxytocin from the posterior pituitary induced by high K + [71] or suckling [72] and that hypotonic stimuli hyperpolarize magnocellular neurosecretory cells via stretch-inactivated channels [73].…”
Section: Specificity Of Cell Swelling-induced Peptide Secretionsupporting
confidence: 86%
“…The trivalent lanthanide GdCl 3 blocks mechanogated channels [44] and also voltage sensitive Ca 2+ channels [reviewed 45]. GdCl 3 in the culture medium does not negatively modify hyposmolarity-or ethanol-induced TRH release from isolated pancreatic islets, hypothalamic PVN or posterior pituitaries [37,38], or prolactin release from acutely dispersed anterior pituitary cells induced by hypotonicity [22,37]. From these experiments it can be concluded that signal leading to exocytosis after cell swelling does not involve GdCl 3 sensitive mechanogated channels.…”
Section: Receptorsmentioning
confidence: 96%
See 3 more Smart Citations